Data security and privacy in the information age in Ecuador. (Innovation & Development in Engineering and Applied Science, 2025)
Digitalization in Ecuador has increased in recent years, and with it the exposure of both personal and organizational data. This exposure increases the risk of cyberattacks. It is necessary to be aware of the risks that currently exist and recommendations for avoiding them. This study presents a systematic literature review with the aim of providing recommendations and recognizing risks in an increasingly digitalized Ecuador, using the PRISMA methodology. It demonstrates that the main threats are sophisticated cyberattacks and a lack of user awareness regarding cybersecurity. Although the Organic Law on Personal Data Protection (LOPDP) exists, there are challenges to its effective implementation. In conclusion, important strategies are presented, such as regulatory frameworks, ongoing staff training on cyberattacks, and the use of new technologies to prevent such cyberattacks. These measures, aligned with international standards, are important for strengthening Ecuador's technological resilience against threats from the digital environment.
Keywords: Information security; data protection; security policies; Ecuador; vulnerabilities; good practices